Strategi Adaptasi Pedagang Pasar Tradisional Dalam Mempertahankan Kelangsungan Usaha Saat Pandemi Covid-19 di Pasar Baru Baturaja - Yosilarasati (Jurnal Empirika, 2024)
Since the emergence of the COVID-19 pandemic, many business actors have experienced a drastic decrease in income due to the lack of buyers; one of the affected business actors is the Baturaja Baru Market trader. The existence of this pandemic makes traders experience stuttering, so it takes work to maintain their business. Therefore, traders are required to make efforts to adapt strategies so that they can continue to keep their business during the pandemic. In this study, the research method used is descriptive qualitative. Data collection techniques used are in-depth interviews, non-participant observation, and documentation. This research uses Suharto's concept of adaptation strategy. The results of this study indicate that the adaptation strategy carried out by traders initially showed a feeling of optimism, but after that, traders began to experience stuttering. Traders who successfully apply the three adaption strategies will arrive at a sound stage and can adapt to the new conditions that existed during the COVID-19 pandemic.